(untitled) (Eurasian Journal of Research, Development and Innovation, 2024)
Thyroid hormones play an important role in many physiological activities, including being important in the proper functioning of the reproductive function of animals, in controlling their development. The thyroid gland directly performs its actions in the activity of the reproductive organs, in particular the sex glands, through its hormones. Excess or lack of thyroid hormones leads to changes in testicular function. In experimental tyreotoxicosis, morphometric indicators of the rat testicular protein Curtain were observed in the experimental group that the curtain thickened in the upper, lower pole and gate Sox, while collagen fiber Tufts also expanded. In the tyreotoxicosis model, it was found that the number of testicular burrowing tubes was slightly reduced, the diameter of the burrowing tube cavity was expanded from this same trait, which decreased the height of the epithelial floor